PENGARUH POTENSI KEBANGKRUTAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ovi Novi Irama (Universitas Dharmawangsa, 2018)
The purpose of this study is to examine the effect of bankruptcy potential with Altman Z-Score modelon stock prices at chemical industry basic manufacturing companies listed in Indonesia StockExchange period 2014 - 2016. The method used in this research is using simple linear regression.The data in this study were obtained by processing the annual financial data of manufacturingcompanies of the basic and chemical industry sectors listed in Indonesia Stock Exchange whichbecome the sample in this research as many as 102 samples with 34 companies. The results showedthat on average the manufacturing companies of the basic and chemical industry sectors listed onthe Indonesia Stock Exchange have a value of 2.1635 which indicates that on average themanufacturing companies of the basic and chemical industry sectors in the Indonesia StockExchange are used as research data this can be predicted to experience failure and Ability variationsof free variables, which in this case is the potential bankruptcy of Altman Z-Score to the variation ofdependent variable that is stock price is equal to 0,135 (13,5%). This means that there are otherfactors (other variables) of 86.5% affecting the price of shares in the Indonesia Stock Exchange